Evolution of Inequality in Nigeria: a Tale of Falling Inequality, Rising Poverty, and Regional Heterogeneity - John Chiwuzulum Odozi; Ruth Uwaifo~Oyelere (Journal of Economics, Race, and Policy, 2023)
Recent research on Nigeria indicates declining income inequality. In contrast, anecdotal evidence suggests that only the upper class has benefited from economic growth in Nigeria over time. The disconnect between these findings and anecdotal evidence, and the limitation in how inequality was estimated in the past literature are the motivation for our research. First, we consider if inequality decreased in Nigeria between 2010 and 2018. We then examine how changes in inequality relate to changes in consumption and poverty. In addition, we examine whether there has been convergence in inequality and consumption across geopolitical regions over this period? Leveraging data from the four waves of the Nigeria General Household Panel Survey (GHS) and carefully measuring inequality in consumption expenditure using Gini, our results suggest that between 2010 and 2018, inequality decreased and median consumption expenditure increased. At the same time, poverty incidence and severity increased precipitously. Our findings also suggest convergence across regions over time in estimated within region Gini. In contrast, we find evidence of divergence across regions over time in median households' consumption.
Keywords: 300; Inequality; Gini; Nigeria; Income distribution; Poverty; Regional disparities